Process of Infection with Bacteriophage φX174: XXXV. Cistron VIII - Funk, Fred D. (1970)
Twenty-two new amber and ochre mutants of φX174 were isolated and classified into complementation groups. Three ochre mutants gave positive complementation tests with reference mutants in the seven previously defined groups and thus represent an eighth cistron. Studies of the physiology of infection in the nonpermissive condition for mutants in cistron VIII yielded the following information. (i) Replicative-form synthesis proceeds at a normal rate, and is turned off at the usual time. (ii) Synthesis of single-stranded deoxyribonucleic acid (DNA) is delayed until nearly 40 min after infection (in the absence of lysis), at which time a slow synthesis of infectious phage particles commences. The synthesis of infectious particles at late times is interpreted as a consequence of “leakage,” and indicates that the cistron VIII product is required in very small quantities. (iii) During the normal period of single-strand synthesis, most of the replicative-form DNA is found in a form with properties similar to those of the transient intermediates of single-strand DNA synthesized during normal infection.